Menerapkan PHBS Dalam Kegiatan Jumbara di Pancur Batu - Yunizar Ritonga; Tia Anggaraini Silalahi; Mhd Nuryansyah Nugraha; Usiono Usiono (Lembaga Pengembangan Kinerja Dosen, 2024)
PHBS is an activity carried out consciously, willing and able to maintain and improve one's health, prevent the risk of disease and protect oneself from the threat of disease and play an active role in the health movement. The application of PHBS must be implemented from an early age so that every group can apply it in everyday life. The aim of this research was to determine the development of PHBS in supporting the healthy lifestyle of members and committees at JUMBARA activities in Pancur Batu District, Deli Serdang Regency.This research used several students and committee members in the health sector who were considered familiar with PMI as samples.Observation, interviews, and documentation were used data collection methods. The articles used were obtained from the Google Scholar database. Based on this research, it was found that PHBS is an effort to create conditions for oneself, family and the environment to play an Active role ini realizing health.